L-dopa reverses behavioral deficits in the Pitx3 mouse fetus - Kleven, Gale A; Booth, Heather M; Voogd, Marco; Ronca, April E (Behavioral neuroscience, 2014)
Studies of fetal rodents have provided evidence that early emerging behaviors, such as the suckling response, are dependent on the developing dopaminergic system. Although connections have been made between manipulations of dopamine and altered behavioral responses, the specific neural pathways involved have yet to be discovered. In this study, we examined the neurobehavioral output of the nigrostriatal pathway, using the Pitx3ak/2J mouse model (Pitx3). Used extensively in the study of Parkinson's disease, the Pitx3 mouse has very specific prenatal loss of dopaminergic neurons solely in the nigrostriatal pathway. Because of this specificity, we hypothesized that behavioral deficits specific to the nigrostriatal pathway would be reversed with administration of the dopamine precursor 3,4-dihydroxyphenylalanine (L-dopa). To test this hypothesis, homozygous mutant and heterozygous control fetal subjects were administered 1 of 4 doses (0, 25, 50, or 75 mg/kg) of L-dopa on the day before birth. Quantification of fetal behavior was scored from video recordings of behavioral observations. The behavioral measures used were (a) spontaneous movement activity; (b) state organization, from quantifications of high- and low-amplitude movements; (c) interlimb movement synchrony, a measure of limb coordination; and (d) oral grasp, similar to a newborn infant suckling response. Specific behavioral deficits observed in the Pitx3 mutants were reversed by L-dopa administration in a dose-dependent manner. However, different deficits required dissimilar doses for reversal, suggesting that some early emerging behaviors may be more sensitive to the administration of L-dopa. Taken together, this study provides valuable information about prenatal behaviors dependent on the nigrostriatal pathway.